SELF-ASSEMBLY OF NANOSCALE POLYMER DOMAINS IN MICROSTRUCTURE TEMPLATE MADE BY AFM MICROMACHINING TECHNIQUE - ZOU XinYu; HUANG YiJun; CONG YanRu; HE YongLing; PAN YuChen; MIAO ZhiBin (Jixie qiangdu)
A mixed top-down/bottom-up hierarchical method was introduced to manufacture massively aligned nanoscale domains’ arrays by using the self-assembly of asymmetrical poly（ styrene-block-ethylene/butylene’s-block-styrene）（ SEBS）triblock copolymers. Silicon substrates of assorted microstructure that is made by AFM that machines approach is used to template the ball-shaped and high-aspect-ratio cylindrical polymer domains’ alignment. The poly domains’ regular arrays were orientated via AFM micromachining technique’s introduction as an implement for dominating triblock copolymers’ self-assembly procedure locally by using the silicon substrate’s topography. This graph epitaxial methodology is exploitable in interbred hard/soft that is condensed substance systems for a variety of applications. Furthermore,pairing bottom-up and top-down methods is a bright,and perhaps basic,bridge between the parallel self-assembly of molecules and the morphological constraint of prevailing technology.